Role of Ubiquitination in Na,K-ATPase Regulation during Lung Injury - Helenius, Iiro T. (American Thoracic Society, 2010)
During acute lung injury edema accumulates in the alveolar space, resulting in hypoxemia due to intrapulmonary shunt. The alveolar Na,K-ATPase, by effecting active Na(+) transport, is essential for removing edema from the alveolar spaces. However, during hypoxia it is endocytosed and degraded, which results in decreased Na,K-ATPase function and impaired lung edema clearance. Na,K-ATPase endocytosis and degradation require the phosphorylation and subsequent ubiquitination of the Na,K-ATPase. These events are the results of cross-talk between post-translational modifications, and how ubiquitination of a specific protein can result from injurious extracellular stimuli. Here, we review current knowledge on the regulation of Na,K-ATPase activity during lung injury, focusing on the role of Na,K-ATPase ubiquitination during hypoxia. A better understanding of these signaling pathways can be of relevance for the design of novel treatments to ameliorate the deleterious effects of acute lung injury.